2009
DOI: 10.3802/jgo.2009.20.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between preoperative serum levels of five biomarkers and relationships between these biomarkers and cancer stage in epithelial overian cancer

Abstract: Objective: To examine the correlation among the preoperative serum levels of five biomarkers presumed to be useful for early detection of epithelial ovarian cancer and evaluate the relationships between serum levels of these five biomarkers and epithelial ovarian cancer stage. Methods: We analyzed 56 newly diagnosed epithelial ovarian cancer patients. Preoperative serum levels of leptin, prolactin, osteopontin (OPN), insulin-like growth factor-II, and CA-125 were determined by ELISA. We also examined the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Elevation of serum prolactin, on the other hand, had also been observed in other malignancies and explored for their potential as diagnostic biomarkers, such as in lung and ovarian cancers [47][51]. However, although shown to be potentially useful as a member of multi-marker diagnostic panels, none of these studies could establish prolactin as an independent cancer marker.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of serum prolactin, on the other hand, had also been observed in other malignancies and explored for their potential as diagnostic biomarkers, such as in lung and ovarian cancers [47][51]. However, although shown to be potentially useful as a member of multi-marker diagnostic panels, none of these studies could establish prolactin as an independent cancer marker.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these authors collected preoperative serum samples from 78 patients with pelvic masses and measured tumor-associated antigens CA-125, CA-15-3, and TAG 72 by immunoradiometric assay in order to evaluate the efficacy of these markers in differentiating benign and malignant pelvic masses, finding that among patients over 50 years of age the three marker combination was associated with a sensitivity of 79% and a specificity of 100% [26]. Another study of 56 newly-diagnosed epithelial ovarian cancer patients, showed that of five serum biomarkers-leptin, prolactin, osteoponin, insulin-like growth factor-II and CA-125-only the preoperative serum CA-125 level had a significant positive correlation with cancer stage ( P <0.01) [27]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of novel markers for ovarian cancer have been identified in recent years, including mesothelin, a 110-kd fragment of epidermal growth factor receptor, lysophophatidic acid, HE4, prostasin, osteopontin, and human kallikreins 6 and 10 [12][13][14][15][16][17][18][19]. Of these, HE4 is one of the most intensively studied of the novel biomarkers.…”
Section: Commentmentioning
confidence: 99%